ANALISIS KESALAHAN BERBAHASA BIDANG MORFOLOGI PADA BERITA VIRTUAL INSTAGRAM EDISI MARET-MEI 2022 - Zyuliah Rifah Dayningrum, (Prosiding Seminar Nasioal Pendidikan Bahasa dan Sastra Indonesia (Senapastra), 2024)
The purpose of this study is to describe the forms of errors in news writing in the field of morphology. This research uses descriptive qualitative method to examine the news. The technique used by researchers to collect data is to find a news story and read it carefully then record the existing errors to be classified according to the study of morphology. The steps in classifying data are, 1) data collection process, 2) identifying errors, 3) classifying errors, 4) evaluating errors. The results in the form of language errors in the field of morphology include 1.) errors in the omission of me- and ber- prefixes, 2) errors in the omission of meN prefixes meng-, mem-, men-, 3.) word writing errors. This research is expected to be an evaluation in order to be more careful in writing news, especially in the field of morphology.